On-chip conductometric detection of short DNA sequences via electro-hydrodynamic aggregation. Issue 1 (24th November 2017) - Venzac, B.; Diakité, M. L.; Herthnek, D.; Cissé, I.; Bockelmann, U.; Descroix, S.; Malaquin, L.; Viovy, J.-L.
Abstract : Label-free, conductometric detection of isothermally amplified bacterial DNA was performed in a portable microfluidic system thanks to electro-hydrodynamic aggregation. Abstract : Fluorescence measurement is the main technology for post-amplification DNA detection in automated systems. Direct electrical reading of DNA concentration in solution could be an interesting alternative to go toward more miniaturized or less expensive devices, in particular in the pathogen detection field. Here we present the detection of short bacterial biomarkers with a direct impedancemetric measurement, within solutions of amplified and elongated DNA sequences in a microchannel. This technology relies on the electrohydrodynamic instability occurring in solutions of long charged macromolecules in a strong electric field. This instability specifically induces the aggregation of long DNAs and triggers conductivity variations that can be monitored by on-contact conductometry. An innovative isothermal amplification and elongation strategy was developed, combining SDA and HRCA reactions, in order to yield long DNAs suitable to be detected by the above principle, from a dilute initial DNA target. In contrast with previous label-free detection methods, this new strategy is very robust to matrix effects, thanks to the unique molecular weight dependence of the instability, coupled with this specific DNA amplification strategy. We demonstrate the detection of a 1 pM gene sequence specific to Staphylococcus aureus, in a portable system.